Effectiveness of Structured Teaching Program on Knowledge Regarding the Use on Spacer Among Parents of Bronchial Asthmatic Children Admitted in the Pediatric Wards in Different Hospitals - Midhu Kurian; Livana PH (GLOBAL HEALTH SCIENCE GROUP, 2020)
Use of spacer among bronchial asthmatic children presents a different set of challenges for their parents. Use of spacer in asthmatic children consider being successful, it requires an accurate understanding by the parents of asthmatic children admitted in the pediatric ward to have adequate skills regarding the use of a spacer. The present study “A study to assess the effectiveness of structured teaching program on knowledge regarding the use of spacer among parents of Bronchial Asthmatic children admitted in the pediatric wards in Different Hospitals, Uttarakhand”. The Objective evaluate the effectiveness of structured teaching program on the use of a spacer among parents of bronchial asthmatic children by comparing pre and post-test knowledge The nature of the study was pre-experimental. The study was conducted in Different Hospitals, Uttarakhand. The research design used for the study was one group pre-test and one group post-test design. Data collected using non-probability convenient sampling. The pilot study was conducted with a constructed tool with which it as found reliable respectively. The data were collected to evaluate the effectiveness of structured teaching program on knowledge regarding the use of spacer among 30 parents of bronchial asthmatic children. The data collected were analysed and interpreted by using descriptive and inferential statistics. Major findings of the study are the highest percentage (53.3%) and the lowest percentage (10%) of the child had suffered from asthma. There is the highest percentage of children 53.3% in the age group of more than 14 years. The education of parents reveals that the highest percentage of 33.3% of mothers and 40% of fathers had secondary education. Pre-test analysis revealed that 90% of parents are having inadequate knowledge and 10% of the parents are having moderate knowledge regarding the use of spacer and that can cause the problems of an asthma attack in children. It can be concluded that pre-test knowledge score was less among parents on asthmatic children. After implementing a structured teaching program the knowledge score was increased. So it was effective in increasing knowledge. Keywords: knowledge; use of spacer; parents; bronchial asthmatic; children